Answer:
7
Explanation:
(h • g)(x) is a composite function, which essentially means that we are looking for h(g(x)), where g(x) replaces x in the function h(x).
We know that h(x) =
and g(x) = x/5. We want: h(g(x)) =
. So, just plug x/5 in for g(x):
![h(g(x))=-2(x/5)^2+9=-2(x^2/25)+9=(-2)/(25) x^2+9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vimztlo4fc4mrdrdeux4wtofx6pi0dqmtn.png)
Now, since we want h(g(-5)), we plug -5 in for x: h(g(-5)) =
![(-2)/(25) (-5)^2+9=(-2)/(25)*25+9=-2 +9=7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3n1t7udy81upxyy6gqfqqlmyl5bawo426g.png)
Thus, the answer is 7.
Hope this helps!